Peningkatan Okupansi Penumpang LRT Sumatera Selatan Dengan Menganalisis Penumpang Integrasi LRT SUMSEL - Yunianto, Aditya; Basri, Hasan (Politeknik Transportasi Darat Indonesia - STTD Bekasi, 2024)
For more than five years of operation, the South Sumatra light train (LRT) occupancy rate has not yet reached the target, so it is necessary to evaluate the program and realize the costs per passenger for South Sumatra LRT transport operators. The implementation methods that will be carried out at the completion of the research are the preparation stage, data collection, analysis and document preparation, evaluation and assistance, and refinement. This results in macro and micro costs for operating the South Sumatra LRT pilot.